2015
DOI: 10.1016/j.ijgo.2014.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Improving maternal and child health systems in Fiji through a perinatal mortality audit

Abstract: The use of PMAs by health workers in Fiji and other Pacific island countries could potentially rectify gaps in maternal and neonatal service delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 15 publications
0
21
0
Order By: Relevance
“…In addition, PNG-specific may not be generalisable to the Pacific region. 3 Raman [35] 2015 Fiji Development and evaluation of a perinatal mortality audit system in 3 hospitals in Fiji. Program evaluation Mixed methods – perinatal audit data and key informant interviews.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, PNG-specific may not be generalisable to the Pacific region. 3 Raman [35] 2015 Fiji Development and evaluation of a perinatal mortality audit system in 3 hospitals in Fiji. Program evaluation Mixed methods – perinatal audit data and key informant interviews.…”
Section: Resultsmentioning
confidence: 99%
“…Other interventions aimed to improve infrastructure, resources and equipment, such as: building staff houses and community health posts, renovations to existing health facilities, and increasing availability of various essential medical supplies, equipment and oxygen provision [ 31 , 32 ]. Several service-specific interventions aimed to improve morbidity and mortality audit systems [ 30 , 33 36 ], management of perinatal deaths and bereavement care [ 35 , 37 ], and antimicrobial prescribing practices [38] .…”
Section: Resultsmentioning
confidence: 99%
“…The profile of neonatal morbidity and mortality in Solomon Islands is comparable to other low‐ and low‐middle income countries where mortality is highest in low birthweight or pre‐term neonates, and most deaths occurring in the first days of life are from intrapartum complications . Other countries in the region face similar challenges.…”
Section: Discussionmentioning
confidence: 87%
“…In Goroka Hospital, Papua New Guinea, very low birth rate, septicaemia and birth asphyxia where the most frequent causes of death for neonates . In Fiji, a study using a perinatal mortality audit showed delays in seeking care, and delay in the provision of adequate care at health facilities contributed to stillbirth and neonatal deaths …”
Section: Discussionmentioning
confidence: 99%
“…Klode et al explained that the failure of professional collaboration was due to a lack of understanding and interpretation that was contrary to the role in collaboration so that the relationship between professionals was not well established [18]. The most common issue for professional is a lack of effective communication and teamwork [19]. In addition, Behruzi et al stated that collaboration in maternal care there are obstacles at the level of interaction such as lack of communication, at the organizational level due to the lack of interest in midwives and different philosophies in practice, and lack of professional resources [20].…”
Section: Discussionmentioning
confidence: 99%